CONCEPTUAL FOUNDATIONS OF SECURITY-ORIENTED ENTERPRISE MANAGEMENT - YEPIFANOVA, Iryna; SHEVCHUK, Yevheniy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article summarizes the conceptual foundations of security-oriented enterprise management. It is established that security-oriented management represents a systemic approach that integrates strategic development priorities with tools for operational risk response. This approach forms the basis for building an effective system for protecting the enterprise’s economic interests by ensuring coherence between current managerial actions and long-term sustainable development goals. Various approaches to defining the essence of the security-oriented enterprise management process have been systematized. The primary objective of security-oriented enterprise management is to ensure resilience, protection, and safety across all dimensions of organizational activity. The object of such a management system is the enterprise’s resilience, understood as a comprehensive characteristic of its ability to maintain integrity, functional efficiency, and dynamic equilibrium under the influence of external and internal destabilizing factors. The effective functioning of a security-oriented management system is based on clearly defined principles that ensure its coherence, adaptability, and effectiveness. Drawing on an in-depth analysis of scientific publications and contemporary approaches to economic security, the key goals of security-oriented management have been identified, forming the conceptual foundation for its practical implementation in business operations. Threat and crisis management constitutes the central element of the security-oriented approach, as it involves a comprehensive analysis of the sources, causes, and characteristics of detected threats, along with the development of strategies for their neutralization. This process encompasses the application of strategic, financial, operational, and risk-management methods, enabling a systematic influence on negative factors and a reduction of their potential impact. Particular attention is devoted to aligning threat-management measures with the enterprise’s long-term development goals. The components of the security-oriented enterprise management process are examined.